Alzheimer's disease medication and outcomes of hospitalisation among patients with dementia. (2020) - Möllers, T.; Perna, L.; Stocker, H.; Ihle, P.; Schubert, I.; Schöttker, B.; Frölich, L.; Bauer, J.; Brenner, H.
Abstract: Aims: The use of Alzheimer disease medication for the treatment of dementia symptoms has shown significant benefits with regards to functional and cognitive outcomes as well as nursing home placement (NHP) and mortality. Hospitalisations in these patient groups are characterised by extended length of stays (LOS), frequent readmissions, frequent NHP and high-mortality rates. The impact of Alzheimer disease medication on the aforementioned outcomes remains still unknown. This study assessed the association of Alzheimer disease medication with outcomes of hospitalisation among patients with Alzheimer disease and other forms of dementia. Methods: A dynamic retrospective cohort study from 2004 to 2015 was conducted which claims data from a German health insurance company. People with dementia (PWD) were identified using ICD-10 codes and diagnostic measures. The main predictor of interest was the use of Alzheimer disease medication. Hospitalisation outcomes included LOS, readmissions, NHP and mortality during and after hospitalisation across four hospitalisations. Confounding was addressed using a propensity score throughout all analyses. Results: A total of 1380 users of Alzheimer disease medication and 6730 non-users were identified. The use of Alzheimer disease medication was associated with significantly shorter LOS during the first hospitalisations with estimates for the second, third and fourth showed a tendency towards shorter hospital stays. In addition, current users of Alzheimer disease medication had a lower risk of hospital readmission after the first two hospitalisations. These associations were not significant for the third and fourth hospitalisations. Post-hospitalisation NHP and mortality rates also tended to be lower among current users than among non-users but differences did not reach statistical significance. Conclusions: Our results indicate that Alzheimer disease medication might contribute to a reduction of the LOS and the number of readmissions in PWD.